The impact of balance specific physiotherapy, intensity of therapy and disability on static and dynamic balance in people with multiple sclerosis: A multi-center prospective study - Pavlikova, M; Cattaneo, D; Jonsdottir, J; Gervasoni, E; Stetkarova, I; Angelova, G; Markova, M; Prochazkova, M; Prokopiusova, T; Hruskova, N; Reznickova, J; Zimova, D; et al. (Multiple sclerosis and related disorders, 2020)
BACKGROUND: A high-quality research identifying the best physiotherapeutic approach for the improvement of balance in people with multiple sclerosis is missing. This study compared aspects of balance improvement such as therapy specificity to balance, therapy method and category, country, intensity and medical conditions. METHODS: A multicentric randomised rater-blinded controlled trial comprised three different physiotherapy programs (Czech and Italian outpatient or inpatient programs). All patients received 20 therapy sessions. Experimental group underwent balance specific physiotherapy (it was Motor Program Activating Therapy in the Czech cohort and Sensory-motor Integration Training in the Italian cohort), control group underwent non-balance specific physiotherapy (it was Vojta reflex locomotion in the Czech cohort and conventional dynamic strengthening exercises in the Italian cohort, respectively). Static balance was evaluated by Berg Balance Scale and dynamic balance was assessed by Timed Up-and-Go Test. RESULTS: A total of 149 patients entered the study. Physiotherapy significantly improved static balance (p < 0.0001, increase by mean 2.6 points (95% confidence interval 2.0-3.5) in BBS score). Balance specific approach had a higher effect than non-specific balance approach (increase in BBS by 1.9 points, 95% confidence interval 0.9-3.7 points). The intensity of the physiotherapy significantly influenced static balance (BBS by 2.7 points higher in the inpatient setting, p= 0.007). Dynamic balance was also improved (TUG decrease by -0.8 s (95% CI -1.4 - -0.1s, p = 0.011)); the balance specificity had no impact. The level of disability played the most important role (p= 0.022). CONCLUSION: Although the overall changes in static and dynamic balance were statistically significant, they were quite small in a clinical sense. A small statistically significant difference between balance specific and non-specific treatment was found. It seems that a high intensity of the therapy is critical to maximize the effectiveness.
Keywords: Male; lidé středního věku; Static and dynamic balance; Single-Blind Method; jednoduchá slepá metoda; terapie cvičením; Prospective Studies; Physiotherapy; Humans; Middle Aged; senioři; Outcome and Process Assessment, Health Care; prospektivní studie; mužské pohlaví; Female; roztroušená skleróza; Multiple sclerosis; Aged; Balance specific approach; posturální rovnováha; ženské pohlaví; Multiple Sclerosis; výsledky a postupy - zhodnocení (zdravotní péče); Adult; Postural Balance; dospělí; lidé; Intensity of therapy; Exercise Therapy